CYP3A5 and CYP3A4, but not ABCB1 polymorphisms affect tacrolimus dose-adjusted trough concentrations in kidney transplant recipients. (February 2014) - Kurzawski, Mateusz; Dąbrowska, Justyna; Dziewanowski, Krzysztof; Domański, Leszek; Perużyńska, Magdalena; Droździk, Marek
Background: Tacrolimus (TAC), acting as a calcineurin inhibitor, is an immunosuppressant widely used after kidney transplantation. TAC requires blood concentration monitoring due to large interindividual variability in its pharmacokinetics and a narrow therapeutic index. Since genetic factors are considered responsible for a part of the observed pharmacokinetic variability, hereby SNPs within the CYP3A4, CYP3A5 and ABCB1 genes in kidney transplant patients of Polish Caucasian origin were investigated.Patients & methods: A total of 241 patients treated with TAC through the first year after kidney transplantation were genotyped for the presence of common SNPs: rs776746:A>G ( CYP3A5*3 ), rs35599367:C>T ( CYP3A4*22 ), rs2740574:A>G ( CYP3A4*1B ) and rs1045642:C>T ( ABCB1 3435C>T) using TaqMan ® assays.Results: CYP3A5 expressers received significantly higher weight-adjusted TAC doses, and were characterized by markedly lower C0 and dose adjusted C0 values in the course of treatment. CYP3A4*1B was significantly associated with TAC pharmacokinetics in univariate analysis. Impact of the CYP3A4*22 allele was significant only at particular time points, that is, 3 months after transplantation, with marginal significance 6 months after transplantation. The ABCB1 genotype did not influence TAC pharmacokinetics. Multivariate analysis of all the studied loci demonstrated that only the CYP3A5*1 (starting from month 1) and CYP3A4*22 alleles (at 3 and 6 months) were independent predictors of TAC dose-adjusted C0 .Conclusion: Our results confirm the impact of the CYP3A4*22 allele on TAC pharmacokinetics, as a second significant genetic factor (in addition to the CYP3A5*1 allele) influencing TAC dose-adjusted blood concentrations in kidney transplant recipients. Original submitted 21 August 2013; Revision submitted 30 September 2013